Classificação citológica dos linfomas caninos - e Suzano, Sara Maria de Carvalho; Sequeira, Julio Lopes [UNESP]; Rocha, Noemi Sousa [UNESP]; Pessoa, Adriana Wanderley de Pinho (My University, 2010)
Lymphoma is among the most frequent canine neoplasia and share many similarities with human non-Hodgkin's lymphoma in respect of etiology, epidemiology, clinical, morphological and immunophenotipical aspects. Human classification schemes have been used in canine lymphoma. The aim of this work was apply Kiel, Working Formulation and Fournel-Fleury's et al. (1994) classification in Fine Needle Aspiration (FNA) cytology matherial. According to Kiel scheme 61.02% (36 cases) were high-grade lymphomas and 38.98% (23 cases) low grade. The Working Formulation, showed 11.86% (7 cases) of low grade, 61.02% (36 cases) intermediary grade and 27.12% (16 cases) high grade. In Fournel-Fleury's protocol revealed a predominance of high-grade lymphoma, with 61.02% (36 cases) over 38.98% (23 cases) of low grade. In conclusion, FNA can be used as a diagnostic method and in canine lymphoma cytological classification. Kiel's system showed the best results, once is based on cytologic basis.
Cytological classification of canine lymphomas
Keywords: Canine; Cytology; Lymphoma